Humanistic Da'wah Implementation: A Case Study of Habib Hussein Ja'far Al-Hadar and His Mad'u - Latifah, Indria Fadhilatul Latifah; Nizar Afandi, Risxi; Muh Slamet Saerozi (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2024)
Communication is a process of delivering messages from the sender or communicator to the recipient or communicant. Communication in da'wah means a preacher including the communicator and mad'u being the communicator. Because in preaching, good communication is also needed so that the message of da'wah can be well received by the mad'u. Da'wah communication also includes specific activities, because in the da'wah process it teaches Islamic teachings. In this paper, we write about Habib Ja'far's way of preaching, where he is an extraordinary preacher, because of his unique way of preaching and being able to adjust the goals of his preaching and pay attention to the condition of the mad'u to be preached to.